2019
DOI: 10.1038/s41467-019-10371-1
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio sp. dhg as a platform for the biorefinery of brown macroalgae

Abstract: Although brown macroalgae holds potential as an alternative feedstock, its utilization by conventional microbial platforms has been limited due to the inability to metabolize one of the principal sugars, alginate. Here, we isolate Vibrio sp. dhg, a fast-growing bacterium that can efficiently assimilate alginate. Based on systematic characterization of the genomic information of Vibrio sp. dhg, we establish a genetic toolbox for its engineering. We also demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 41 publications
0
52
1
Order By: Relevance
“…V. natriegens intrinsically has many desirable characteristics for a bioproduction chassis: Fast growth rate, genetic tractability, biological safety, and growth on a wide variety of carbon sources [4][5][6][7][8][9][10][11][12][13]46]. In regards to growth rate in particular, it has been shown that expression of some heterologous genes can decrease expression of others, due to competition for finite resources in the cell such as RNA polymerase and ribosomes [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…V. natriegens intrinsically has many desirable characteristics for a bioproduction chassis: Fast growth rate, genetic tractability, biological safety, and growth on a wide variety of carbon sources [4][5][6][7][8][9][10][11][12][13]46]. In regards to growth rate in particular, it has been shown that expression of some heterologous genes can decrease expression of others, due to competition for finite resources in the cell such as RNA polymerase and ribosomes [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Second, as V. natriegens has garnered interest as an emergent chassis, genetic tools have been developed [8,10,12]. In concert with this, its extremely fast growth rate assists in genetically engineering this organism [7,12,13]. Third, its tolerance to high salt-in some media, up to 30 g·L −1 (~0.51 M) with an optimum at 15 g·L −1 (~0.26 M)-coupled to fast growth could help maintain axenic fermentation conditions without expensive antibiotic techniques; high salt tolerance has been referenced as an advantage for other emergent chassis such as Halomonas which grows in 60 g·L −1 NaCl [7,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we introduced each of the genes derived from E. coli W3110 and recently isolated Vibrio sp. dhg (Table 1) [23]. The overexpression was conducted by using the P tac promoter and synthetic 5 -UTRs (Table S1) designed for maximum translational levels [38].…”
Section: Validation Of Enhanced Lycopene Production With Expression Omentioning
confidence: 99%
“…Although the MEP pathway requires more energy (ATP) and cofactors (NADPH) to synthesize IPP than the MVA pathway [13], the direct use of the two C-3 glycolytic intermediates enables MEP pathway to have a 1.48-fold higher IPP yield (0.83 C-mole/C-mole) than the MVA pathway (0.56 C-mole/C-mole) [13,22]. Since most bacteria showing fast growth inherently possess the MEP pathway for synthesizing their building blocks [21], the MEP pathway has been widely utilized in recent studies for lycopene production [10,23]. Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation